Demand-side management via optimal production scheduling in power-intensive industries: The case of metal casting process. (1st September 2018) - Ramin, D.; Spinelli, S.; Brusaferri, A.
Highlights: Unified framework for participation of production plants in energy and reserve market. MILP model integrating production and electricity market aspects. Optimal scheduling for cost minimization in day-ahead energy market. Exploitation of residual flexibility in capacity market. Abstract: The increasing challenges to the grid stability posed by the penetration of renewable energy resources urge a more active role for demand response programs as viable alternatives to a further expansion of peak power generators. This work presents a methodology to exploit the demand flexibility of energy-intensive industries under Demand-Side Management programs in the energy and reserve markets. To this end, we propose a novel scheduling model for a multi-stage multi-line process, which incorporates both the critical manufacturing constraints and the technical requirements imposed by the market. Using mixed integer programming approach, two optimization problems are formulated to sequentially minimize the cost in a day-ahead energy market and maximize the reserve provision when participating in the ancillary market. The effectiveness of day-ahead scheduling model has been verified for the case of a real metal casting plant in the Nordic market, where a significant reduction of energy cost is obtained. Furthermore, the reserve provision is shown to be a potential tool for capitalizing on the reserve market as a secondary revenue stream.